College Student Perceptions About Librarian Directed Presentations in the Blended Learning Environment - Levesque, Donna; Kunnapas, Tiia (Qualitative and Quantitative Methods in Libraries, 2017)
Many students do not realize that specialized skills are needed to interact with information. This quantitative research study investigated student perceptions about library skills, library resources, and whether presentations conducted by a librarian changed their perceptions and ultimately improved their academic performance. The quantitative evidence supports the need for instructional library programming.